The impact of physical activity and sedentary behaviors on frailty levels. (June 2019) - Kehler, Dustin Scott; Theou, Olga
Highlights: Physical activity can reduce the prevalence or severity of frailty. Sedentary behaviors are associated with frailty independent of physical activity. There are few clinical trials examining the impact of physical activity on frailty. Interventions are needed which limit sedentary behaviors to manage frailty. Abstract: Heterogeneity in aging can be explained by frailty. Lifestyle behaviors such as physical activity can help manage frailty levels. Conversely, sedentary behaviours are associated with frailty independently of physical activity. Here, we summarize epidemiological and clinical trial evidence concerning the impact of physical activity and sedentary behaviors on frailty levels. We also analysed the National Health and Nutrition Examination Survey (NHANES) data to describe physical activity and sedentary behavior accumulation patterns across frailty levels and their impact on mortality risk. The few prospective and intervention studies demonstrate that higher physical activity levels are associated with a lower incidence of frailty. There are no interventions published which limit sedentary behaviors to manage frailty. Using the NHANES data we demonstrate that individuals are less likely to meet physical activity guidelines and are more likely to accumulate sedentary time in prolonged bouts. Prolonged sedentary bouts and total sedentary time were associated with a higher mortality risk in frail individuals but not in the fit group. Non-bouted sedentary time was not associated with mortality risk. Our review and novel data suggest that there is a need for more intervention studies which focus on increasing physical activity or minimizing sedentary time to manage frailty levels.